A Modified Quadrature Birdcage Coil Incorporated With a Curved Feature for In Ovo MR Imaging - Chang-Hoon Choi; Maximilian Bruch; Suk-Min Hong; Sandra Krause; Carina Stegmayr; Stefan Schwan; Wieland A. Worthoff; Jorg Felder; N. Jon Shah (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: This study presents a novel MRI coil design approach explicitly tailored for chick embryo measurements, with the primary objective of improving sensitivity and coverage. Methods: The limitations posed by conventional birdcage coils were addressed by introducing a curvature feature into a standard coil. The performance of the modified coil was assessed using EM simulations and experimental evaluations, which were subsequently validated using a 7 T MRI scanner. A comparative analysis was conducted against a standard quadrature low-pass birdcage coil to evaluate key factors. Results: The proposed coil demonstrated improved SNR and uniformity, particularly in the proximity of the end-rings. These results were consistent with the findings obtained from the simulations. Conclusions: The use of our innovative birdcage coil design holds promise and offers practical potential for in ovo studies.